Raman spectroscopic investigation of the human liver stem cell line HepaRG - Ryabchykov, Oleg; Braeutigam, Katharina; Galler, Kerstin; Neugebauer, Ute; Mosig, Alexander; Bocklitz, Thomas; Popp, Jürgen (Journal of Raman Spectroscopy, 2018)
In this work, Raman spectroscopic cell imaging approaches and a discrimination between HepG2, nondifferentiated hepatic stem cell line HepaRG, and differentiated hepatocyte-like HepaRG cells are presented. Raman spectroscopic imaging was used to visualize the cell nuclei by means of false color imaging using a marker band, and a cell segmentation was performed by means of clustering. Furthermore, a 3-class-classification model based on the mean Raman spectra of individual cells was established for a classification between different cell types. A high average sensitivity of 96% was achieved by the applied classification model. Based on the results of clustering and classification, the main spectral contributions to different cell types and cell segments were analyzed in detail. Thereby, HepG2, nondifferentiated hepatic stem cell line HepaRG, and differentiated hepatocyte-like HepaRG cells were Raman spectroscopically characterized and proven to be significantly different.
CRIS-Team Scopus Importer:2023-04-20
Keywords: HepaRG; HepG2; Raman spectroscopic imaging